Comparison between Antioxidant Effect of Vitamin-C Alone and its Combination to Vitamin-E in Long Evans Norwegian Rat (Bangladesh Journal of Physiology and Pharmacology, 2010)
In rat myocardial damage was produced the administration of adrenaline in a dose of 2 mg/kg body weight (b.w.) subcutaneously for 2 consecutive mornings. This damage was assessed indirectly by significant increase in serum aspertate transminase (AST) and directly by microscopic changes in the myocardium.Pretreatment with the vitamin-C in a dose 10mg/kg body weight subcutaneously and preteatment with the combination of vitamin-C in a dose of 10mg/kg b.w. subcutaneously and vitamin-E in a dose of 50mg/kg b.w. orally for 10 days prevented the adrenaline induced myocadial damage equally which was evidenced by the equal prevention in the rise of serum AST & LDH levels as well as equal prevention of microscopic changes of the myocardium by the adrenaline. DOI: 10.3329/bjpp.v23i1.5726Bangladesh J Physiol Pharmacol 2007; 23(1&2) : 16-19